Sulfate metabolites provide an intracellular pool for resveratrol generation and induce autophagy with senescence - Patel, Ketan R; Andreadi, Catherine; Britton, Robert G; Horner-Glister, Emma; Karmokar, Ankur; Sale, Stewart; Brown, Victoria A; Brenner, Dean E; Singh, Rajinder; Steward, William P; Gescher, Andreas J; Brown, Karen (Science translational medicine, 2013)
The phytochemical resveratrol has been shown to exert numerous health benefits in preclinical studies, but its rapid metabolism and resulting poor bioavailability may limit translation of these effects to humans. Resveratrol metabolites might contribute to in vivo activity through regeneration of the parent compound. We present quantitation of sulfate and glucuronide conjugates of resveratrol in human plasma and tissue after repeated ingestion of resveratrol by volunteers and cancer patients, respectively. Subsequent pharmacokinetic characterization of a mixture of resveratrol-3-O-sulfate and resveratrol-4'-O-sulfate in mice showed that these metabolites are absorbed orally but have low bioavailabilities of ~14 and 3%, respectively. Sulfate hydrolysis in vivo liberated free resveratrol, which accounted for ~2% of the total resveratrol species present in mouse plasma. Monosulfate metabolites were also converted to the parent in human colorectal cells. The extent of cellular uptake was dependent on specific membrane transporters and dictated antiproliferative activity. Sulfate metabolites induced autophagy and senescence in human cancer cells; these effects were abrogated by inclusion of a sulfatase inhibitor, which reduced intracellular resveratrol. Together, our findings suggest that resveratrol is delivered to target tissues in a stable sulfate-conjugated form and that the parent compound is gradually regenerated in selected cells and may give rise to the beneficial effects in vivo. At doses considered to be safe in humans, resveratrol generated via this route may be of greater importance than the unmetabolized form.